One new species of Baburia Koçak, 1981 and one of Metendothenia Diakonoff, 1973 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand - Jirasuttayaporn, Panaka; Pitaktunsakul, Piyaporn; Pinkaew, Nantasak (Zootaxa, 2018)
Two new species of the tribe Olethreutini are described and illustrated from Thailand: Baburia paucustriga Jirasuttayaporn and Pinkaew, n.sp., and Metendothenia ordospina Jirasuttayaporn and Pinkaew, n.sp. The two new taxa increase the number of described species in Baburia to three and in Metendothenia to 14.